Generic and Disease-specific Health-related Quality of Life in Pediatric Intestinal Failure. Issue 3 (24th September 2021) - McCaig, Jessica K.; Henry, Owen S.; Stamm, Danielle A.; Dorval, Gaby; Hurley, Alexis; Han, Sam M.; Hong, Charles R.; Staffa, Steven J.; Modi, Biren P.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objective: The aim of the study was to assess overall and disease-specific health-related quality of life (hrQOL) in patients with pediatric intestinal failure (PIF) and caregivers and elucidate differences from healthy and chronic gastrointestinal (GI) illness cohorts. Methods: Cross-sectional study of patients with PIF and their caregivers managed at a multidisciplinary intestinal rehabilitation program using the PedsQL Generic Core and the Gastrointestinal Symptoms Module to assess generic and disease-specific hrQOL, respectively. These data were compared to established healthy and chronic GI disease controls. Results: A total of 53 patients (mean age 6.2 ± 3.9 years) and their caregivers were studied. Patients reported lower generic hrQOL than healthy children (73.0 vs 83.84, P < 0.001), but no difference from patients with chronic GI disease (73.0 vs 77.79). In contrast, PIF caregivers perceived similar generic hrQOL compared to a healthy cohort (78.9 vs 82.70), but higher when compared to the GI disease cohort (78.9 vs 72.74, P < 0.01). Patients with PIF and caregivers reported lower psychosocial health scores than healthy controls. Patients and caregivers reported similar disease-specific hrQOL to a cohort with chronic GI disease but significantly lower disease-specific hrQOL than a healthy cohort ( P < 0.001 both groups). Conclusions: Patients with PIF and their caregivers have disparate perceptions of generic hrQOL when compared to healthy and chronic GI disease controls. Both patients and caregivers, however, had significantly lower scores in psychosocial health than healthy controls. In addition, disease-specific hrQOL was substantially lower than healthy controls for PIF patients and caregivers. Further investigation to expand on these findings and identify modifiable variables to improve the psychosocial health score and disease-specific factors would be of high value.